Using Artificial Intelligence in Data Analytics - Stavytskyi, O. V.; Pantyeyev, R. L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
This article explores the transformation of data analytics under the influence of artificial intelligence technologies. It analyzes the key differences between traditional analytical methods and AI-driven approaches, emphasizing automation, scalability, and precision. The role of machine learning, natural language processing (NLP), and other technologies in modern analytics is discussed. The paper outlines the stages of data processing using AI and practical aspects of implementing such solutions in business environments. Special attention is given to an overview of three leading tools – Tableau, Power BI, and Google AutoML. The study demonstrates how AI reshapes decision-making by providing deeper insights and enhancing operational efficiency.